Preference and consumption of mud crab Scylla serrata on natural low cost crab food and pellets. - Toledo, Darwin L. (2004.)
This study is focused on determining preference and consumption in dry weight and wet weight of juvenile mud crab Scylla serrata hatched artificially and reared in tanks, in four foods. These foods were: pellets, trash fish, brown mussel meat and cow hide. Results showed that highest preference by juvenile mud crab was on trash fish, brown mussel, followed by pellets and cow hide, though not significantly different. Highest consumption in dry weight was on trash fish, followed by brown mussel meat and pellets, though not significantly different and lastly, cow hide. Results also showed that highest consumption by juvenile mud crabs on pellets, followed by trash fish brown mussel and cow hide though not significantly different.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mud Crabs; Scylla Serrata